2020
DOI: 10.1158/1538-7445.am2020-445
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 445: Integrated proteogenomic characterization across seven histological types of pediatric brain tumors

Abstract: We performed a comprehensive proteogenomic analysis across seven major types of childhood brain tumors for a deeper understanding of their functional biology. Whole genome seq, RNAseq, quantitative proteomic and phosphoproteomic profiling were performed on 219 fresh frozen tumor samples representing the histologic diagnoses of: low grade astrocytoma (93), ependymoma (32), high grade astrocytoma (26), medulloblastoma (22), ganglioglioma (18), craniopharyngioma (16) and atypical teratoid rhabdoid tumor (12). Cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 0 publications
0
37
0
Order By: Relevance
“…Ryall et al 17 described rare KIAA1549::BRAF fusion breakpoints (15:11) in two infants with disseminated pLGG who had poor outcomes. Our study builds on this by showing that rare/novel KIAA1549::BRAF fusion breakpoints, including 15:11, are highly enriched in recurrent/progressive pLGGs within PNOC001 and external cohorts 44,45 and predict worse clinical outcomes in PNOC001. We found these breakpoints enriched in young patients (younger than 3 years) and patients with a supratentorial midline PA.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Ryall et al 17 described rare KIAA1549::BRAF fusion breakpoints (15:11) in two infants with disseminated pLGG who had poor outcomes. Our study builds on this by showing that rare/novel KIAA1549::BRAF fusion breakpoints, including 15:11, are highly enriched in recurrent/progressive pLGGs within PNOC001 and external cohorts 44,45 and predict worse clinical outcomes in PNOC001. We found these breakpoints enriched in young patients (younger than 3 years) and patients with a supratentorial midline PA.…”
Section: Discussionmentioning
confidence: 67%
“…Our study builds on this by showing that rare/novel KIAA1549:: BRAF fusion breakpoints, including 15:11, are highly enriched in recurrent/progressive pLGGs within PNOC001 and external cohorts 44,45 and predict worse clinical outcomes in PNOC001.…”
Section: Discussionmentioning
confidence: 68%
“…The Clinical Proteomic Tumor Analysis Consortium (CPTAC) has reported a range of tumor-tissue studies that are not necessarily HT but have sample sizes larger than 100 [128][129][130][131][132][133][134][135][136] and are thus worth mentioning in this review. These studies focus on proteogenomic analysis, identifying cancer-relevant pathways or potential therapeutic targets.…”
Section: Applications Of Ht Proteomics In Biomedical Studiesmentioning
confidence: 99%
“…They are poorly represented by gene expressions as proteins employee complex, multi-level post translational modification that are not reflected at the mRNA level. Studies that quantified both mRNA gene expressions and proteomic abundances identified a median correlation of <0.5 in lung [5] and many other tissues [6, 7]. Therefore, identifying and validating genes and pathways at protein level that are associated with ACE2 is crucial for further understanding the roles of this gene in coronavirus infection.…”
Section: Introductionmentioning
confidence: 99%
“…The second group focuses on associations by leveraging pre-estimated cell-type composition for cell-type controlled or specific effects. For example, cell-type composition estimates are often treated as covariates in simple association analysis for “unconfounded” effects [6, 7]. Cell-type specific associations are also considered by modeling interactive effects between the estimated cell-type composition and covariates [26] or by considering hierarchical mixture models to decompose the observed tissue-level traits into their values in different cell types for their cell-type specific associations [27].…”
Section: Introductionmentioning
confidence: 99%